A cross sectional study to assess the prevalence of malocclusion in 08-12 years old school age children of the selected urban & rural community of Bangladesh - Faria Tabassum Tanni; Tanzila Rafique; Tanjila Akter; Khanum Huzzatun Nahar Khawla Binta Harun; Gazi Shamim Hasssan (Update Dental College Journal, 2021)
Objective: To determine the prevalence of malocclusion in school-age children from a selective area of the urban and rural community of Bangladesh.